2014
DOI: 10.1007/s00586-014-3422-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growing rod lengthening technique on the sagittal spinal and the spinopelvic parameters

Abstract: Significant improvement was found in the global thoracic kyphosis angle, by comparing the preoperative, the early postoperative and the last follow-up parameters statistically (p < 0.05). There was no statistically significant improvement in the spinopelvic parameters (p > 0.05). We claim that growing rod technique doesn't provide statistically significant improvement, in the sagittal spinal and the spinopelvic parameters, except for the kyphosis, in the treatment of EOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…It has been reported that there is a small increase in PI values during growth and during the growing-rod lengthenings [8,9,11,17]. Similar to the result found in our study, Atici et al [19] found a decrease in the PI during lengthening, which was not statistically significant. In our study, the pelvic parameters PT and SS showed no significant change during the treatment, in agreement with the literature.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been reported that there is a small increase in PI values during growth and during the growing-rod lengthenings [8,9,11,17]. Similar to the result found in our study, Atici et al [19] found a decrease in the PI during lengthening, which was not statistically significant. In our study, the pelvic parameters PT and SS showed no significant change during the treatment, in agreement with the literature.…”
Section: Discussionsupporting
confidence: 86%
“…In a previous study, Atici et al [19] evaluated 23 EOS patients who underwent growing-rod surgery. They found a significant improvement in the global TK angle on comparing the preoperative, the early postoperative, and the last follow-up parameters, and no significant improvement in the spinopelvic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled average SSI rate was calculated to be 1.6% (median, 2.8%; range, 0.2%–18.3%) based on 64 cohorts comprising a total of 212,639 patients. Patients who underwent instrumented spinal fusion procedures were evaluated for SSIs in 35 identified studies [6,12,25,28,35,37,39,48,50,61,67,74,77,78,84,85,90,93,97,98,101,112,121,122,126,127,132,134,135,137,148,154,156,160,174]. The pooled average SSI rate was calculated to be 3.8% (median, 4.2%; range, 0.4%–20%) based on 39 cohorts with a total of 28,628 patients.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that repeated distraction forces associated with rib anchors in the VEPTR construct may be more kyphogenic, which could pose a risk of kyphosis gain with the VEPTR during the lengthening period. In previous studies, 3,6,18,19 it was revealed that GRI can effectively correct hyperkyphotic EOS, with the sagittal pro-file successfully restored to a normal range. The change in sagittal plane alignment reveals that GRI has a strong tendency to decrease TK in patients with a preoperative hyperkyphotic sagittal modifier.…”
Section: Discussionmentioning
confidence: 99%